Endogenous NUCB2/Nesfatin-1 Regulates Energy Homeostasis Under Physiological Conditions in Male Rats - Wilz, Anna-Maria; Wernecke, Kerstin; Appel, Lena; Kahrs, Johanna; Dore, Riccardo; Jöhren, Olaf; Lehnert, Hendrik; Schulz, Carla (Hormone and Metabolic Research, 2020)
Nesfatin-1 is the proteolytic cleavage product of Nucleobindin 2, which is expressed both in a number of brain nuclei (e. g., the paraventricular nucleus of the hypothalamus) and peripheral tissues. While Nucleobindin 2 acts as a calcium binding protein, nesfatin-1 was shown to affect energy homeostasis upon central nervous administration by decreasing food intake and increasing thermogenesis. In turn, Nucleobindin 2 mRNA expression is downregulated in starvation and upregulated in the satiated state. Still, knowledge about the physiological role of endogenous Nucleobindin 2/nesfatin-1 in the control of energy homeostasis is limited and since its receptor has not yet been identified, rendering pharmacological blockade impossible. To overcome this obstacle, we tested and successfully established an antibody-based experimental model to antagonize the action of nesfatin-1. This model was then employed to investigate the physiological role of endogenous Nucleobindin 2/nesfatin-1. To this end, we applied nesfatin-1 antibody into the paraventricular nucleus of satiated rats to antagonize the presumably high endogenous Nucleobindin 2/nesfatin-1 levels in this feeding condition. In these animals, nesfatin-1 antibody administration led to a significant decrease in thermogenesis, demonstrating the important role of endogenous Nucleobindin 2/nesfatin-1in the regulation of energy expenditure. Additionally, food and water intake were significantly increased, confirming and complementing previous findings. Moreover, neuropeptide Y was identified as a major downstream target of endogenous Nucleobindin 2/nesfatin-1.
Keywords: NUCB2; Nesfatin-1; energy expenditure; hypothalamus; PVN; NTS